2008
DOI: 10.1111/j.1365-2362.2008.02055.x
|View full text |Cite
|
Sign up to set email alerts
|

A study for maternal thyroid hormone deficiency during the first half of pregnancy in China

Abstract: Background Maternal thyroid hormone deficiency is the most common disorder of thyroid function during pregnancy and can influence the outcome for mother and foetus. The purpose of this study was to investigate the prevalence of thyroid hormone deficiency during the first half of pregnancy in iodine sufficient areas of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 20 publications
6
45
1
Order By: Relevance
“…In this study, we evaluated the prevalence of thyroid dysfunction by screening 2899 pregnant women using the first trimester-specific reference intervals from our previous work (10). The results showed that high-risk women, classified based on Endocrine Society Clinical Practice Guidelines (9), had more than a 1.5-fold increased risk of hypothyroidism (subclinical or overt) and a 1.7-fold increased risk of hyperthyroidism (subclinical or overt) during early pregnancy than did women in the non-high-risk group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we evaluated the prevalence of thyroid dysfunction by screening 2899 pregnant women using the first trimester-specific reference intervals from our previous work (10). The results showed that high-risk women, classified based on Endocrine Society Clinical Practice Guidelines (9), had more than a 1.5-fold increased risk of hypothyroidism (subclinical or overt) and a 1.7-fold increased risk of hyperthyroidism (subclinical or overt) during early pregnancy than did women in the non-high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…The first trimester-specific reference intervals used to diagnose thyroid dysfunctions were based on those determined previously (10). The first trimester-specific reference ranges for TSH, FT 4 , and FT 3 were 0.13-3.93 mIU/l, 12.00-23.34 pM, and 3.46-7.70 pM respectively.…”
Section: And Diagnostic Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown lower prevalence estimates of hypothyroidism among pregnant women [14][15][16][17][18]. One of the reasons for this discrepancy is thought to be the gestational age at which screening is performed.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of this special hormonal state during pregnancy varies among wide intervals, depending on the iodine status of the geographical area, the trimester-specific hormonal assays and the used normal ranges, thus according to these influencing factors published data showed an incidence ranging between 1.3-26.5% (Casey et al, 2007;Vaidya et al, 2007;Clear-Goldman et al, 2008;Berbel et al, 2009;Moleti et al, 2009;Shan et al 2009;Hendrichs et al, 2010). The prevalence is the lowest in the first gestational trimester (1.2-3.2%) but than it starts to increase gradually during the II.…”
Section: Iodine Dose (μG/day) Organization and Date Median Urinary Iomentioning
confidence: 99%